Indonesia Dijajah Lebih dari 300 Tahun? Memahami Penjajahan Sebagai Proses Transformasi Struktural - Shofwan Al Banna Choiruzzad (Department of International Relations, Universitas Andalas, 2021)
Despite its public popularity, the claim that Indonesia was colonized by the Dutch for more than 300 years is now considered by historians as a historical myth, established as an instrument for nation-building. This article argues that rather than simply judging the claim as myth, we must understand it more comprehensively by employing the framework of International Political Economy, especially the approach which put the entanglements of Capitalism and Colonialism at the center of its analysis. By understanding Colonialism-Imperialism as a process (or a set of processes) of structural transformation, this article contends that the claim that Indonesia had been colonized by the Dutch for more than 300 years has its own merit and must be further explored.